PENGEMBANGAN MODUL FIKIH BERBASIS INQUIRY LEARNING DI KELAS VIII MADRASAH TSANAWIYAH NEGERI II MANDAILING NATAL - Inayah Putri, Rizki; Iskandar, Topan (Edu Global : Jurnal Pendidikan Islam, 2023)
Rizki Inayah Putri, NIM. 18010036 (2022), thesis title: "Development of Inquiry Learning-Based Jurisprudence Module in Class VIII MTsN 2 Mandailing Natal". Islamic Religious Education Study Program, Mandailing Natal State Islamic College. The problem in this research is the lack of Jurisprudence teaching materials that can be used in class VIII MTsN 2 Mandailing Natal. The purpose of this study was to find out the description of the Jurisprudence learning process, the validity and practicality of developing teaching materials in the form of Inquiry Learning-based Jurisprudence modules in class VIII MTsN 2 Mandailing Natal on the beauty of sharing with alms, grants and gifts. The method used in this research is research and development (research and development). With a 4D approach (Define, Design, Developed, Disseminate). The data collected in this study were obtained through needs analysis instruments, validity instruments and practicality instruments. The Fiqh module based on Inquiry Learning in class VIII MTsN 2 Mandailing Natal was declared valid by the four validators with a percentage score on the objective aspect of 99% very valid, the rationality aspect 98% very valid, the content aspect of the module was 98% very valid, and the language aspect was 96 % is very valid. The validation as a whole gets a very valid 95% score from the four validators. Based on the results of the questionnaire analysis of students' responses to the practicality of using the Fiqh module, it was found that this module was practically used in learning with an average acquisition of above 90%. The item statement obtained an average questionnaire value of 89%. In addition to using student response questionnaires, the practicality of using the modules that have been developed can also be seen from the validation results of teacher response questionnaires, which get an average value of 96% with very practical information. Based on the results of the validity and practicality that have been carried out by researchers in the module on Inquiry Learning-based Jurisprudence for class VIII MTsN 2 Mandailing Natal it can be used in the learning process.